2021
DOI: 10.1186/s12879-021-06853-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of single human papillomavirus 53 infection: a retrospective study of 419 cases

Abstract: Background Human papillomavirus (HPV) infection is the main cause of cervical cancer. Characteristics of HPV infections, including the HPV genotype and duration of infection, determine a patient’s risk of high-grade lesions. Risk quantification of cervical lesions caused by different HPV genotypes is an important component of evaluation of cervical lesion. Data and evidence are necessary to gain a deeper understanding of the pathogenicity of different HPV genotypes. The present study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…To be noted, HPV53 ranked second in the present study, which was similar to the report in Xi'an [18]. However, the pathogenicity of single HPV53 infection was low [45]. Besides HR-HPV, the present study also investigated the prevalence distribution of LR-HPV.…”
Section: Discussionsupporting
confidence: 86%
“…To be noted, HPV53 ranked second in the present study, which was similar to the report in Xi'an [18]. However, the pathogenicity of single HPV53 infection was low [45]. Besides HR-HPV, the present study also investigated the prevalence distribution of LR-HPV.…”
Section: Discussionsupporting
confidence: 86%
“…As the second most carcinogenic genotype in the world, HPV18 ranks only fourth in some Chinese areas or is not even in the top five in other provinces ( Li et al, 2016 ; Zhang et al, 2018 ). Moreover, HPV53 is the fourth or fifth most prevalent genotype in most areas of China ( Sun et al, 2017 ; Chen et al, 2019 , 2021 ; Jiang et al, 2019 ; Wang et al, 2019 , 2022 ; Zhang et al, 2019 , 2020 ; Li et al, 2020 ; Luo et al, 2020 ), and is the most prevalent genotype among healthy women in other Asian countries ( Ouh et al, 2018 ). Our study also demonstrated that HPV81 was the most common low-risk type, with the same overwhelming advantage in other Chinese provinces ( Zhao et al, 2018 ; Chen et al, 2019 ; Zhang et al, 2019 ; Luo et al, 2020 ; Yan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic strains include the following: 16,18,31,33,35,39,45,51,52,56,58,59 and 66 [31]. HPV-53 is also considered potentially high risk, but it has low pathogenicity and slow rates of progression [32]. Of these high-risk varieties, HPV-16 and HPV-18 are most strongly associated with cancer occurrence [33,34], and HPV-16 is a relatively common strain [35].…”
Section: Overview Of Hpv Infection and Oncogenicitymentioning
confidence: 99%